Suatu Kajian Empiris tentang Pengaruh Evaluasi Dimensi Kualitas Produk Tahan Lama Terhadap Perilaku Niat Membeli Kembali - Charles Makmur Sianturi (LP2MTBM MAKARIOZ, 2018)
Intention to purchase has been the focus of researchers for long time but the study on intention to repurchase is very few.The purpose of this study to test empirically the effects of quality on intention to repurchase of durable good. For this research intention to repurchase is defined as the willing of consumers to buy and to consume a certain product after having experiences of the product. According to the purpose of the study eight dimensions of quality is measured by Likert scale in relation to intention to repurchase. Data is collected by survey research with self administered questionnaires. The number of respondents is targeted for one hundred, consist of student at one of the private universities in Medan who has only one cell phone as the object of the research. Multiple regression analysis is applied to test the effect of quality on intention to repurchase of durable goods. The coefficients of multy regression shown each of eight dimensions of quality has positif coeffisiens and significant. Based this analysis can be concluded that quality has significant effects on intention to repurchase of durable goods.